Case Report: Chronic pancreatitis in children as the cumulative effect of bilio-pancreatic abnormalities and genetic mutations - Destro, Francesca; Durante, Eleonora; Salerno, Raffaele; Campari, Alessandro; Meroni, Milena; Diotto, Veronica; Brunero, Marco; Pelizzo, Gloria (Frontiers in Pediatrics, 2024)
Pancreatitis, in general, is a high-morbidity condition. Genetic conditions and anatomic variants are sometimes seen, especially in children, where biliary etiologies and alcohol are less common than in adults. The decision to intervene, the combined operative-endoscopic strategy, and the timing pose unique challenges. We report the case of a 10-year-old boy with PRSS1 mutation and pancreatic duct duplication, discussing the management and reviewing the recent reports in the Literature.Recent data have demonstrated a high prevalence of genetic mutations among pediatric patients with RP and CP. In particular, mutations that most commonly play a crucial role in the etiology of CP are associated with the PRSS1 (gene-encoding cationic trypsinogen), SPINK1 (Serine Protease Inhibitor Kazal type 1), CFTR (cystic fibrosis), CTRC, and CPA1 genes 2 . All these mutations impact pancreatic